Impact of High-Altitude Hypoxia on Bone Defect Repair: A Review of Molecular Mechanisms and Therapeutic Implications - Chen, Pei; Liu, Yushan; Liu, Wenjing; Wang, Yarong; Liu, Ziyi; Rong, Mingdeng (Frontiers in Medicine, 2022)
Reaching areas at altitudes over 2,500–3,000 m above sea level has become increasingly common due to commerce, military deployment, tourism, and entertainment. The high-altitude environment exerts systemic effects on humans that represent a series of compensatory reactions and affects the activity of bone cells. Cellular structures closely related to oxygen-sensing produce corresponding functional changes, resulting in decreased tissue vascularization, declined repair ability of bone defects, and longer healing time. This review focuses on the impact of high-altitude hypoxia on bone defect repair and discusses the possible mechanisms related to ion channels, reactive oxygen species production, mitochondrial function, autophagy, and epigenetics. Based on the key pathogenic mechanisms, potential therapeutic strategies have also been suggested. This review contributes novel insights into the mechanisms of abnormal bone defect repair in hypoxic environments, along with therapeutic applications. We aim to provide a foundation for future targeted, personalized, and precise bone regeneration therapies according to the adaptation of patients to high altitudes.